Integrative analysis of geographic variation and species boundaries in the white-lipped pitviper complex (Squamata: Viperidae: Crotalinae: Trimeresurus albolabris) - Anita Malhotra; Mrinalini Walter; Guillem Limia Russel; Roger S. Thorpe (Vertebrate Zoology)
Abstract In this study, we present a comprehensive analysis of species in the Trimeresurus albolabris complex (comprising the white-lipped pitviper, its former subspecies, and closely related species) to identify genetic and phenotypic lines of evidence to assess whether these taxa represent independently evolving lineages or populations with wide-ranging variants. Our morphometric data set includes over 400 live and preserved specimens spanning almost the entire range of T. albolabris sensu stricto and its relatives. We compare patterns of differentiation in three mitochondrial gene fragments for over 300 specimens and conduct a population genetic analysis of nuclear NT3 sequences from over 200 specimens. This level of detail allowed us to identify instances of incongruence between morphological affinities, mitochondrial clades, and nuclear haplotype distribution in putative taxa throughout Indochina. Although recently described species from this region, including T. salazar, T. caudornatus, and T. uetzi, are related to T. septentrionalis in the mitochondrial phylogeny, they extensively share nuclear haplotypes with the purpureomaculatus group, particularly with T. erythrurus. The most common haplotype of T. albolabris sensu stricto is also present throughout Indochina. However, populations in southern Indochina and western Java are morphologically differentiated, belong to distinct mitochondrial clades, and have a high proportion of private NT3 alleles. As they appear to intergrade extensively with populations further north, we herein resurrect the Javan taxon Bothrops viridis var. fario Jan, 1859 as a nomen for this population at the subspecies level, as Trimeresurus albolabris fario comb. nov. Furthermore, we lower the rank of taxa from the extensive zone of intergradation that stretches from Myanmar to central Vietnam to that of subspecies under T. albolabris (T. a. guoi) or T. septentrionalis (T. s. salazar, T. s. caudornatus, and T. s. uetzi), pending detailed further investigations of the extent of gene flow between them and other recognised species in the complex.